Istikhdāmu Wasīlatu Bāzl ‘Alā Tarqiyyati Mahārati Al Kitābati Li Aṭ Ṭullābi Al Fasl Aṡ Ṡāmin Fī Al Madrasah Aṡ Ṡanāwiyyah Al Hukūmiyyah Yaftif Ayyā Gadang Basāmān Garbiyyah - Yulianti, Welly; Arsya, Fajriyani; Dewi, Yelfi; Rizal, Eka (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
An effort to improve students' educational success is choosing the right teaching medium and getting students' attention. The method used in this study is puzzle, which is a method that teachers can develop using simple materials and tools to help students understand the learning material. The purpose of this study is to know the use of the puzzle method in learning Arabic to improve writing ability. Accordingly, the researcher conducted this study entitled "Using the Puzzle Method to Improve the Writing Skill of Eighth Grade Students in the Middle School Yaftif Gadang West Pasaman. This study uses research and qualitative data from observations, interviews, and documents. The teacher prepares the generated Basler method. The puzzles are then randomly selected if the students can arrange them correctly, and the students are then scored as successful if the students still do not understand the material. So if they can put Puzzle together, they can create a set of vocabulary in Puzzle. From this it can be concluded that there is a lack of effectiveness between teachers and students, as the teacher thinks that the students have understood the lesson, while the students are still unable to understand it because they do not repeat what they have learned at home because they are not only learning at school but at home Also, yes, until we understand more about teaching